The Relationship between CmADHs and the Diversity of Volatile Organic Compounds of Three Aroma Types of Melon (Cucumis melo) - Chen, Hao; Cao, Songxiao; Jin, Yazhong; Tang, Yufan; Qi, Hongyan (Frontiers in Physiology, 2016)
Alcohol dehydrogenase (ADH) plays an important role in aroma volatile compounds synthesis of plants. In this paper, we tried to explore the relationship between CmADHs and the volatile organic compounds (VOCs) in oriental melon. Three different aroma types of melon were used as materials. The principle component analysis of three types of melon fruit was conducted. We also measured the CmADHs expression level and enzymatic activities of ADH and alcohol acyl-transferase (AAT) on different stages of fruit ripening. An incubation experiment was carried out to investigate the effect of substrates and inhibitor (4-MP, 4-methylpyrazole) on CmADHs expression, ADH activity and the main compounds of oriental melon. The results illustrated that ethyl acetate, hexyl acetate (E,Z)-3,6-nonadien-1-ol and 2-ethyl-2hexen-1-ol were the four principal volatile compounds of these three types of melon. AAT activity was increasing with fruit ripening, and the AAT activity in CH were the highest, whereas ADH activity peaked on 32 DAP, two days before maturation, and the ADH activity in CB and CG were higher than that in CH. The expression pattern of 11 CmADH genes from 24 to 36 day after pollination (DAP) was found to vary in three melon varieties. CmADH4 was only expressed in CG and the expression levels of CmADH3 and CmADH12 in CH and CB were much higher than that in CG, and they both peaked two days before fruit ripening. Ethanol and 4-MP decreased the reductase activity of ADH, the expression of most CmADHs and ethyl acetate or hexyl acetate contents of CB, except for 0.1mM 4-MP, while aldehyde improved the two acetate ester contents. In addition, we found a positive correlation between the expression of CmADH3 and CmADH12 and the key volatile compound of CB. The relationship between CmADHs and VOCs synthesis of oriental melon was discussed.